Tanfīdz Barnāmij Al-Lughah Al-‘Arabiyyah Fī Ma’had As-salām Kampar Riau : Baina Al-Ittīshalāt, Wa Al-Qiyādah, Wa Al-Isyrāf - Nurul Fadhilah Fakaubun; Nurul Elmira Harmeilinda; Zakiyah Arifah (LISANUDHAD: JURNAL BAHASA, PEMBELAJARAN DAN SASTRA ARAB, 2021)
Islamic boarding schools (Pesantren) are growing in the world of education. Pesantren also has various programs proclaimed to develop the Arabic language, so many programs aim to improve Arabic language skills at the As-Salam Kampar Islamic boarding school. As for the program's implementation, namely communication, leadership, and supervision. This study aims to analyze and find a model for implementing language programs in Pondok Pesantren Assalam Kampar. This research used descriptive qualitative, where the instrument is the researchers as a human instrument. At the same time, the data collection techniques are observation, interviews, documentation, and validity techniques using triangulation. The researchers have interviews with the principal related to the management of the implementation of the Arabic language program at Pondok Pesantren Assalam Kampar; communication, leadership, and supervision that the principal had carried out in running the Arabic language program.  The results showed; 1) the communication is input and output in the program management process, where communication is identical with social interaction; in this case, the communication process carried out by the chairman is bottom-up communication; 2) The leadership is intended to influence a group. Towards the achievement of goals, it is also implemented in the form of participatory leadership. 3) At the same time, supervision which implies looking very carefully at work as a whole, is also carried out in this Pesantren, the form of democratic supervision.